1999
DOI: 10.1074/jbc.274.4.2532
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Tyrosine Hydroxylase mRNA Stability by Protein-binding, Pyrimidine-rich Sequence in the 3′-Untranslated Region

Abstract: The stability of mRNA for tyrosine hydroxylase (TH), the rate-limiting enzyme in catecholamine synthesis, is regulated by oxygen tension in the pheochromocytomaderived PC12 cell line. We previously identified a pyrimidine-rich 27-base-long protein-binding sequence in the 3-untranslated region of TH mRNA that is associated with hypoxia-inducible formation of a ribonucleoprotein complex (hypoxia-inducible protein-binding site (HIPBS)). In this study, we show that HIPBS is an mRNA stabilizing element necessary fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 22 publications
7
89
1
Order By: Relevance
“…1A). Protein binding to 3Ј-UTR pyrimidine-rich segments of for example TH and erythropoetin mRNA has been implicated in both constitutive and regulated stability control of the messenger (25,29). In line with this notion, we have presently observed specific binding of a 55-60-kDa protein to the ins-PRS RNA oligonucleotide.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…1A). Protein binding to 3Ј-UTR pyrimidine-rich segments of for example TH and erythropoetin mRNA has been implicated in both constitutive and regulated stability control of the messenger (25,29). In line with this notion, we have presently observed specific binding of a 55-60-kDa protein to the ins-PRS RNA oligonucleotide.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, there may be a requirement of other cis-acting mRNA elements to obtain full control of glucoseinduced changes in mRNA stability. The induced stability of TH mRNA in response to hypoxia is for instance dependent of protein interactions with both the 3Ј-UTR and the coding region of the mRNA (29).…”
Section: Discussionmentioning
confidence: 99%
“…There are many similarities between the regulation of ␣1(I) collagen mRNA in activated HSCs and the regulation of ␣-globin and lipoxygenase mRNAs in erythroid cells and the tyrosine hydroxylase mRNA in response to hypoxia (17,(47)(48)(49). These mRNAs form a class of molecules post-transcriptionally regulated via 3Ј-UTR interactions with protein(s).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, much of the evidence compiled to date suggests that the internal initiation of translation on both type I and type II picornavirus IRES elements requires certain trans-acting cellular proteins in addition to canonical translation initiation factors (for reviews, see Jackson & Kaminski, 1995;Stewart & Semler, 1997)+ In this study, we investigated the process of translation as directed by the IRES elements of poliovirus (PV), coxsackievirus strain B (CVB), human rhinovirus (HRV), encephalomyocarditis virus (EMCV), and foot-andmouth disease virus (FMDV)+ Specifically, we examined whether these picornaviruses, representing four of the six picornavirus genera, require the cellular protein, PCBP2, for viral translation+ PCBP2 is a cellular RNA-binding protein that interacts with the 59 NCR of poliovirus RNA (Dildine & Semler, 1992;Blyn et al+, 1995Blyn et al+, , 1996+ The protein contains three hnRNP K-homologous (KH) RNA-binding domains and has a binding preference for poly(rC)+ PCBP2 mRNA is widely expressed and has been localized both in the cytoplasm and the nucleus (Leffers et al+, 1995)+ To date, the only known functions attributed to PCBP2 are its functional associations with the 39 NCRs of the a-globin and the tyrosine hydroxylase mRNAs in complexes that impart stability (Kiledjian et al+, 1995;Paulding & Czyzyk-Krzeska, 1999)+ Similar complexes have also been found to form on the 39 NCRs of lipoxygenase, a(I)-collagen, and erythropoietin mRNAs (Holcik & Liebhaber, 1997;Czyzyk-Krzeska & Bendixen, 1999)+ In addition to the role of PCBP2 in cellular mRNA stability, a number of additional functions relating to viral infection have been ascribed to the protein+ We have previously shown that the interaction of PCBP2 with the poliovirus 59 NCR performs dual functions in the life cycle of the virus by facilitating the initiation of both viral protein synthesis and viral RNA synthesis (Blyn et al+, 1997;Parsley et al+, 1997)+ Likewise, Andino and colleagues confirmed this functional duality and proposed that PCBP could also function in a mechanism involving accessory proteins of viral origin to regulate the processes of translation and replication (Gamarnik & Andino, 1997)+ In addition to its documented functions in the poliovirus life cycle, PCBP2 also plays a role in the translation of HAV genomic RNA (Graff et al+, 1998)+ Furthermore, human papillomavirus type 16 (HPV16), a member of the Papovaviridae, has evolved a mechanism to utilize PCBP2+ For HPV16, PCBP2 acts as a regulator of late gene expression (Collier et al+, 1998)+ This work investigates the possibility that RNA binding by PCBP2 is a general requirement for the internal initiation of translation on picornavirus IRES elements+ Competition RNA mobility-shift assays conducted with 32 P-labeled PV stem-loop IV RNA, recombinant PCBP2 (rPCBP2), and five different picornavirus 59 NCRs confirmed a conserved physical interacti...…”
Section: Introductionmentioning
confidence: 99%